Safety Assessment of High-Purity, Synthetic Nicotinamide Riboside (NR-E) in a 90-Day Repeated Dose Oral Toxicity Study, With a 28-Day Recovery Arm. (July 2020) - Marinescu, Anca G.; Chen, Jayson; Holmes, Holly E.; Guarente, Leonard; Mendes, Odete; Morris, Mark; Dellinger, Ryan W.
Nicotinamide riboside (NR) is a naturally occurring form of vitamin B3 shown to preferentially elevate the nicotinamide adenine dinucleotide (NAD+) metabolome compared to other vitamin B3 forms (nicotinic acid and nicotinamide). Although daily requirements of vitamin B3 are typically met through the diet, recent studies have shown that additional supplementation with NR may be an effective method to counter the age-related decline in NAD+ levels as NR bypasses the rate-limiting step in NAD+ biosynthesis. Furthermore, pharmaceutical applications of NR for age-related disorders have been proposed. In this study, the safety of a high-purity, nature-identical, synthetic NR (NR-E), manufactured under the guidelines of good manufacturing practices for dietary supplements (21 CFR 111) as well as for drugs (21 CFR 210), was investigated in a 90-day oral toxicity study in Sprague Dawley rats at 300, 500, and 1, 200 mg/kg/d. There were no mortality or clinical observations attributable to the test substance at any dose. A small but statistically significant decrease in body weight was observed at day 92 in the 1, 200 mg/kg/d NR-treated male rats only. In contrast to a previously published safety assessment using a different synthetic NR (NIAGEN), whose no-observed-adverse-effect-level (NOAEL) was reported to be 300 mg/kg/d, there were no adverse changes in clinical pathology parameters and no notable macroscopic or microscopic findings or treatment-related effects at similar doses. In the current study, the NOAEL for systemic toxicity of NR-E in Sprague-Dawley rats was conservatively determined to be 500 mg/kg/d for males (solely based on body weight) and 1, 200 mg/kg/d for females.